Irfani Epistemology and the Practice of Sholat 40: Intuitive Knowledge in the Syattariyah Tariqah of West Sumatra - Adlan Sanur Tarihoran; Kaharuddin Kaharuddin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines the implementation of Irfani epistemology in the practice of Sholat 40 (forty consecutive days of ritual prayer) within the Syattariyah Tariqah in West Sumatra, focusing on its role as a medium for attaining intuitive knowledge (ma‘rifah). While previous studies on Sufi orders in Indonesia often emphasize ritual practices or social functions, few have analyzed their epistemological dimensions. Adopting a phenomenological approach, supported by literature review and in-depth interviews with followers and the murshid, this research identifies three key elements within Sholat 40: soul purification (tazkiyah al-nafs), mystical experience, and the attainment of intuitive knowledge of the Divine essence. The findings indicate that in Irfani epistemology, knowledge transcends rational cognition and emerges through inner experience, enabling practitioners to perceive the presence of God directly. This study argues that Sholat 40 functions not only as ritual worship but also as a structured epistemic practice that facilitates spiritual transformation, moral refinement, and personal growth. By situating this practice within Irfani epistemology, the article contributes to broader discourses on Islamic mysticism, experiential knowledge, and the living tradition of Sufi epistemologies in Southeast Asia.